Few‐Layer Black Phosphorus Nanosheets as Electrocatalysts for Highly Efficient Oxygen Evolution Reaction. Issue 19 (14th June 2017) - Ren, Xiaohui; Zhou, Jie; Qi, Xiang; Liu, Yundan; Huang, Zongyu; Li, Zhongjun; Ge, Yanqi; Dhanabalan, Sathish Chander; Ponraj, Joice Sophia; Wang, Shuangyin; Zhong, Jianxin; Zhang, Han
Abstract: Black phosphorus (BP) is a new rediscovered layered material, which has attracted enormous interests in the field of electrocatalysis. Recent investigations reveal that bulk BP is a promising electrocatalyst for oxygen evolution reactions (OER), whereas its bulk crystal structure restricts sufficient active sites for achieving highly efficient OER catalytic performances. Toward this end, few‐layer BP nanosheets prepared by facile liquid exfoliation are applied as electrocatalysts and exhibit preferable electrocatalytic OER activity in association with structural robustness; subsequently, the dependence of current density and applied bias potential on the concentration of OH − has also been uncovered. Most importantly, we are aware that reduction in the thickness of BP nanosheets would generate extra active sites from the ultrathin planar structure and complimenting to the electrocatalytic activities. It is further anticipated that the current work might provide further implementation about the OER performance of BP nanosheets, thereby, offering extendable availabilities for BP‐based electrocatalysts in constructing high‐performance OER devices. Abstract : Few‐layer black phosphorus (BP) nanosheets demonstrate preferable electrocatalytic oxygen evolution reactions (OER) behavior as well as high stability in KOH electrolyte. Besides that, further accelerating the centrifugation speed can result in extra active sites and improve the electrochemical OER performance of BP nanosheets. This work provides implementation about BP nanosheets and selective centrifugation approach in constructing high‐performance OER devices.